Fodder productivity and profitability of different maize and legume intercropping systems - GINWAL, DEVENDRA SINGH; KUMAR, RAKESH; RAM, HARDEV; DUTTA, SUSANTA; ARJUN, MALLIK; HINDORIYA, P S (The Indian Journal of Agricultural Sciences, 2019)
The current trend in global agriculture is to search for highly productive, sustainable and eco-friendly cropping systems. Intercropping of cereals with legumes is a recognized practice for economizing the use of nitrogenous fertilizers and increasing the productivity, quality, and profitability particularly in commercial grain crops but possibilities of fodder production in these intercropping systems is less explored. Availability of green fodder with improved quality to animals is the key to success of dairy enterprises and it is difficult to maintain the health and milk production of the livestock without supply of the quality green fodder. The growing of fodder crops in mixture with legumes has potential to improve palatability and digestibility of fodder (Kumar et al. 2018, Kumar et al. 2016). It is fact that about 65-70% of the total cost of livestock farming is attributed to feeding. However, green fodder production is a good way in order to curtail the cost on feed and fodder resources for sustainable livestock production. At present, the country is facing a net deficit of 35.6% green fodder, 10.95% dry crop residues and 44% concentrate feed ingredients. At the current level of growth in forage resources, there will be 18.4% deficit in green fodder and 13.2% deficit in dry fodder by the year 2050 (Anonymous 2015). The main objective of intercropping has been to maximize use of resources such as space, light and nutrients as well as to improve fodder quality and quantity. When legumes are used as intercrops, they provide beneficial effect on soil health by fixing atmospheric nitrogen, improving physical, chemical and biological properties. Hence, present study was undertaken in order to to assess the productivity, soil nutrient status and economics of different forage maize-legumes based intercropping systems.